Sympathetic mediation of salivation induced by intracerebroventricular pilocarpine in rats - Cecanho, R.; Anaya, M.; Renzi, Antonio [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, L. A. (Elsevier B.V., 1999)
Central cholinergic activation by pilocarpine induces salivation dependent on the integrity of forebrain areas. The present work investigates the autonomic mediation of this salivation. Pilocarpine (500 nmol/rat) was injected into the lateral ventricle (LV) of tribromoethanol-anesthetized adult male rats. Preweighed cotton balls were inserted into the oral cavity and weighed again 7 min later. ol-adrenoceptor antagonists (3-50 mu mol/kg) prazosin (alpha(1)), yohimbine (alpha(2)) or propranolol (beta) injected intraperitoneally (i.p.) produced, 80%, 20% and 0% inhibition respectively of the LV pilocarpine-induced salivation. Intracerebroventricular injections (160 nmol) of the antagonists did not alter the effects of pilocarpine injected into the LV. Bilateral section of chorda tympani nerve or bilateral sympathetic cervical ganglionectomy produced 0% and 40% inhibition of pilocarpine-induced salivation, respectively. Ganglionectomy did not alter salivation induced by i.p, injection of pilocarpine (4 mu mol/kg). The results indicate that there is a large sympathetic contribution to the salivation induced by central cholinergic activation. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: cholinergic receptors; adrenoceptors; cervical ganglion; chorda tympani; salivary glands; lateral ventricle; saliva